Sell Low and Buy High: Arbitrage and Local Price Effects in Kenyan Markets* - Burke, Marshall; Bergquist, Lauren Falcao; Miguel, Edward (Quarterly Journal of Economics, 2019)
Large and regular seasonal price fluctuations in local grain markets appear to offer African farmers substantial intertemporal arbitrage opportunities, but these opportunities remain largely unexploited. Small-scale farmers are commonly observed to “sell low and buy high,” rather than the reverse. In a field experiment in Kenya, we show that credit market imperfections limit farmers’ abilities to move grain intertemporally. Providing timely access to credit allows farmers to buy at lower prices and sell at higher prices, increasing farm revenues and generating a return on investment of 29%. To understand general equilibrium (GE) effects of these changes in behavior, we vary the density of loan offers across locations. We document significant effects of the credit intervention on seasonal price fluctuations in local grain markets, and show that these GE effects shape individual-level profitability estimates. In contrast to existing experimental work, the results indicate a setting in which microcredit can improve firm profitability, and suggest that GE effects can substantially shape microcredit’s effectiveness. In particular, failure to consider these GE effects could lead to underestimates of the social welfare benefits of microcredit interventions.